CITIZEN PARTICIPATION’S HISTORY AND POLITICAL CULTURE IN MEXICO CITY. BETWEEN SYSTEMIC CONDITIONING AND CIVIL DREAMS (Andamios, Revista de Investigación Social, 2004)
This paper deals with the history of institutionalized citizen participation in Mexico City. However, it doesn’t attempt to make a thorough account of facts, mechanisms, instances and legal instruments which, dating from 1928 until the present day, preceded and characterized its building and formal development in this capital city. What this brief historical review particularly aims at, is at showing how was born a set of relations, practices and perceptions, that characterize a particular political culture, through the construction and functioning of “diverse” institutional modes along history. This current political culture is part of a symbolic universe that embodies traditions and customs that explain, to a very large extent, citizen participation’s achievements and limitations within Mexico’s capital city.